2014
DOI: 10.1002/2014gl061397
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for superterminal raindrops

Abstract: A network of optical disdrometers (including laser precipitation monitors and a two-dimensional video disdrometer) was utilized to determine whether the recent reports of "superterminal" raindrops were spurious results of drop breakup occurring on instrumentation. Results unequivocally show that superterminal raindrops at small (less than 1 mm) sizes are ubiquitous, are measurable over an extended area, and appear in every rain event investigated. No evidence was found to suggest that superterminal drops are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…It is evident here that the distribution of superterminal and subterminal drops vary with the drop diameter (Larsen et al, ). Superterminal raindrops are mainly observed at 0.5‐mm diameter, and subterminal raindrops become dominant above 0.5 mm in diameter.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It is evident here that the distribution of superterminal and subterminal drops vary with the drop diameter (Larsen et al, ). Superterminal raindrops are mainly observed at 0.5‐mm diameter, and subterminal raindrops become dominant above 0.5 mm in diameter.…”
Section: Resultsmentioning
confidence: 73%
“…Thurai et al () observed the broadening of fall speed distribution with a significant skewness during the passage of an intense convective rain event, which is due to the asymmetric horizontal mode of oscillations of raindrops. Larsen et al () and Montero‐Martínez and García‐García () evidenced the presence of superterminal (higher than terminal velocity) and subterminal (lower than terminal velocity) fall speeds in intense rain events. More recently, Bringi et al () also showed the existence of superterminal and subterminal raindrops from an optical probe and Two‐Dimensional Video Disdrometer (2DVD) measurements.…”
Section: Introductionmentioning
confidence: 97%
“…The occurrence of super‐terminal drops with small sizes under calm wind conditions, particularly for the 31 August 2007 case when R was 75 mm h −1 , reinforces previous observations (Montero‐Martínez et al ., ; Larsen et al ., ) that indicate the preponderance of super‐terminal drops in the presence of large raindrops (i.e. during periods of high rainfall rates).…”
Section: Resultsmentioning
confidence: 99%
“…However, since Montero‐Martínez et al . () documented their presence, several authors have confirmed that super‐terminal drops are not the result of instrumental effects (Thurai et al, ; Larsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The other disdrometers in the array were used to confirm that two‐dimensional video disdrometer was operating properly during each of the events studied here. A thorough description of the instrument array and site environment is presented in Larsen et al [], Jameson et al [, ], Larsen and Teves [], and Larsen et al [], but a detailed site analysis is beyond the scope of this manuscript.…”
Section: Datamentioning
confidence: 99%